Peran Pendidikan Keluarga dalam Menghadapi Tantangan Revolusi Industri 4.0 - Tulak, Riany Bara (PEADA': Jurnal Pendidikan Kristen, 2023)
Education in the Industrial Revolution 4.0 era is considered a development effort that includes the ability to think, act and live life in a global environment. It can be said that today's digital media has become a major need for most people. Individuals and digital media based on internet services are like a stamp that cannot be separated or released which is then attached and becomes a definition for each other. The existence of technology for communication and information is like a double-edged sword. On the one hand, it can provide the advantage of intensity and speed in delivering messages, these internet network-based services intersect directly with daily activities in the real world, on the other hand it actually increases the complexity of interactions that can cause stress. From this situation, it is often found that families are strangers to each other, misunderstandings occur, they feel that they are not cared for and understood by their families so that it results in feelings of loneliness and even depression. Family education as the first educational institution for children, has a very big role in realizing children's dreams. The function of the family as an educational institution has a significant role in equipping children with positive values ​​as a basis for further education. Even though humans have positive potential for development, the realization of this potential is greatly influenced by the special role of family education, especially in facing the era of industrial revolution 4.0. Family education currently plays an important role in directing and guiding children by providing positive examples so that they are ready and able to face the challenges of the industrial revolution 4.0. Keywords: family role, family education, challenges, parenting, industrial revolution 4.0 Education in the Industrial Revolution 4.0 era is considered a development effort that includes the ability to think, act and live life in a global environment. It can be said that today's digital media has become a major need for most people. Individuals and digital media based on internet services are like a stamp that cannot be separated or released which is then attached and becomes a definition for each other. The existence of technology for communication and information is like a double-edged sword. On the one hand, it can provide the advantage of intensity and speed in delivering messages, these internet network-based services intersect directly with daily activities in the real world, on the other hand it actually increases the complexity of interactions that can cause stress. From this situation, it is often found that families are strangers to each other, misunderstandings occur, they feel that they are not cared for and understood by their families so that it results in feelings of loneliness and even depression. Family education as the first educational institution for children, has a very big role in realizing children's dreams. The function of the family as an educational institution has a significant role in equipping children with positive values ​​as a basis for further education. Even though humans have positive potential for development, the realization of this potential is greatly influenced by the special role of family education, especially in facing the era of industrial revolution 4.0. Family education currently plays an important role in directing and guiding children by providing positive examples so that they are ready and able to face the challenges of the industrial revolution 4.0. Keywords: family role, family education, challenges, parenting, industrial revolution 4.0